Tradisi Rongga dan Kedudukan Hak Ulayat Masyarakat Nggolonio terhadap Pendatang di Desa Nggolonio Kabupaten Nagekeo - Maria Metriani Eva Ili; Darius Mauritisus; Petornius Damat (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The indigenous Nggolonio community gave land to newcomers (Dhajong) with the mandate that this land was only for making settlements, surviving and earning a living and not for other interests. However, the Dhajong community used this land for the construction of public facilities, the indigenous community of Nggolonio Village questioned the implementation of the mandate from their ancestors. The research used was empirical legal research with a qualitative approach. Data collection for this research was interviews and document studies. The results of the study indicate that the position of the customary rights of the Nggolonio Community against the rights of the Dhajong immigrant community, customary rights are the collective rights of the indigenous community to a certain area that is inherited from generation to generation. This right includes control and management of land and the natural resources above it. In the context of immigrant communities, access to and use of customary land is usually regulated by customary mechanisms that apply in the local community. This can involve the involvement of special agreements or land use permits that are mutually agreed upon between the indigenous community and immigrants. It is important to note that each indigenous community has different rules and mechanisms in managing relations between indigenous communities and immigrants. Therefore, a deep understanding of customary law and local practices in Nggolonio Village is essential to obtain an accurate picture of the status of customary rights of indigenous peoples and the rights of immigrant communities in the area.